A novel approach based on untargeted lipidomics reveals differences in the lipid pattern among durum and common wheat. (1st February 2018) - Righetti, Laura; Rubert, Josep; Galaverna, Gianni; Hurkova, Kamila; Dall'Asta, Chiara; Hajslova, Jana; Stranska-Zachariasova, Milena
Graphical abstract: Highlights: Untargeted metabolomics revealed differences between common and durum wheat lipidome. The statistical models were validated by using two independent sample sets. Authentic durum wheat and adulterated admixture (3% adulteration) were discriminated. Putatively identified markers were evaluated applying ROC curves, giving AUC >90%. Abstract: In the present work the possibility of using an untargeted metabolomic strategy to discriminate between common and durum wheat lipidome for an authenticity purpose was explored. A first study was conducted by analyzing 52 samples from two durum and common wheat varieties. Afterwards, an extended and independent sample set (173 samples and five varieties) was used as a confirmatory study to verify the stability and consistency of the models obtained. Putatively identified markers were evaluated applying ROC curves resulting in individual marker AUC >90% both in preliminary and confirmatory study. In addition, digalactosyl diglyceride (DGDG) 36:4 was shown to be an effective marker differentiating between authentic durum wheat and its adulterated admixture down to 3% adulteration level, which is the maximum contamination level allowed by Italian legislation. The results demonstrated that untargeted lipidomics, in conjunction with chemometric tools has a significant potential for screening and detection of wheat fraud.